Organic Nutrients Induced Coupled C- and P-Cycling Enzyme Activities During Microbial Growth in Forest Soils - Loeppmann, Sebastian; Breidenbach, Andreas; Spielvogel, Sandra; Dippold, Michaela A.; Blagodatskaya, Evgenia (Frontiers in Forests and Global Change, 2020)
Besides environmental and soil physical drivers, the functional properties of microbial populations, i.e. growth rate, enzyme production and maintenance requirements are dependent on the microbes’ environment. The soil nutrition status and the quantity and quality of the substrate input, both infer different growth strategies of microorganisms. It is uncertain, how enzyme systems respond during the different phases of microbial growth and retardation in soil. The objective of this study was to uncover the changes of microbial functioning and their related enzyme systems in nutrient-poor and nutrient-rich beech forest soil during the phases of microbial growth. We determined microbial growth via kinetic approach by substrate-induced respiratory response of microorganisms, enabling the estimation of total and growing biomass of the microbial community. To induce microbial growth we used glucose, while yeast extract simulated additional input of nutrients and factors indicating microbial residues (i.e. necromass compounds). Microbial growth on glucose showed a 12–18 h delay in associated enzyme activity increase or the absence of distinct activity responses (Vmax). β-glucosidase and chitinase (NAG) demonstrated clear differences of Vmax in time and between P-rich and P-poor soils. However, during microbial growth on glucose + yeast extract, the exponential increase in enzymatic activity was clearly stimulated accompanied by a delay of 8–12 h, smoothing the differences in nutrient-acquisition dynamics between the two soils. Furthermore, cross-correlation of β-glucosidase and acid phosphatase between the two sites demonstrated harmonized time constraints, which reflected the establishment of comparable and balanced enzymatic systems within the decomposition network. The network accelerated nutrient acquisition to maintain microbial growth, irrespective of the contrasting soil properties and initial nutrient stocks, indicating similar tradeoffs of C- and P- cycling enzymes in both soils. This reflects comparable temporal dynamics of activities in nutrient-poor and nutrient-rich soil when the glucose + yeast extract was added. During lag phase and phase of exponential microbial growth, substrate turnover time of all enzymes was shortened in nutrient-poor forest soil exclusively, reflecting that the quality of the added substrate strongly matters during all stages of microbial growth in soil.